Synthesis of Flower-like Silver Nanostructures on Silicon and Their Application in Surface-enhanced Raman Scattering - Minh, Kieu Ngoc; Anh, Cao Tuan; Ngan, Luong Truc Quynh; Vu, Le Van; Cao, Dao Tran (Communications in Physics, 2017)
To enhance the intensity of surface-enhanced Raman scattering (SERS), production of metal nanostructures with sharp points, lying side by side at the nanometer level plays an extremely important role. In this paper, we report on a manufacturing process in which the silver nanoparticles with the flower-like shape have been fabricated. Such silver nanoparticles have been fabricated by chemical deposition of silver particles on silicon wafers, using a solution of hydrofluoric acid (HF), silver nitrate (AgNO3) and ascorbic acid (AsA) in water, at room temperature. During the manufacturing we found that only when the concentrations of AgNO3 and AsA are appropriate, the flower-like silver nanoparticles will form. Note that while other authors mainly made flower-like silver nanoparticles in the form of suspensions, we have created flower-like silver nanoparticles with cabbage-shape on a silicon surface. The ensembles of flower-like silver nanoparticles above were used as SERS substrates to detect crystal violet (CV) in low concentrations and good results were obtained.